HUKUMAN MATI BAGI PENGEDAR NARKOBA DALAM PERSPEKTIF HUKUM ISLAM - Zainuddin Abdullah (STIT AL-AMIN KREO TANGERANG, 2018)
In the early of Islam, the meaning of khamr is kind of intoxicating drinks that they are made from grape, dates, wheat and so on. The meaning of khamr experiences development either from kind, name and its danger that follows the development of time. In Islamic law, for the dealer of Narkoba with certain scale can be categorized as criminal act (Ḥirābah), extraordinary crime and because of that threatened with Ḥudūd sentence such as death sentence. It suits the spirit of Maqāṣid al-Syarī’ah especially about al-Darūriyyah al-Khams.